2003
DOI: 10.1093/qjmed/hcg126
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoedema: an underestimated health problem

Abstract: Chronic oedema is a common problem in the community with at least 100 000 patients suffering in the UK alone, a problem poorly recognized by health professionals. Lymphoedema arising for reasons other than cancer treatment is much more prevalent than generally perceived, yet resources for treatment are mainly cancer-based, leading to inequalities of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
328
2
14

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(363 citation statements)
references
References 10 publications
19
328
2
14
Order By: Relevance
“…26 Lymphoscintigraphy, a nuclear medicine imaging technique, along with other imaging technologies, have been used to investigate the pre-and post-operative risk of lymphoedema development in patients with breast cancer. [27][28][29] The uptake of this imaging modality in the clinical diagnostic process is not universal 30 and is the topic of continuing experimental evaluation. 31 New technologies such as bioimpedance may aid diagnosis and provide a level of accuracy in clinical examination not previously possible through traditional measurement techniques such as circumferential measures.…”
Section: Breast Cancer-related Lymphoedemamentioning
confidence: 99%
See 1 more Smart Citation
“…26 Lymphoscintigraphy, a nuclear medicine imaging technique, along with other imaging technologies, have been used to investigate the pre-and post-operative risk of lymphoedema development in patients with breast cancer. [27][28][29] The uptake of this imaging modality in the clinical diagnostic process is not universal 30 and is the topic of continuing experimental evaluation. 31 New technologies such as bioimpedance may aid diagnosis and provide a level of accuracy in clinical examination not previously possible through traditional measurement techniques such as circumferential measures.…”
Section: Breast Cancer-related Lymphoedemamentioning
confidence: 99%
“…The health costs of management of BCRL are not available in the literature, however Moffatt et al 30 reported that in South West London 29% of people identified with lymphoedema experienced an acute infection in the affected area over the previous year with 27% being admitted for intravenous antibiotics. Mean length of stay for this condition was 12 days, and the estimated mean cost was £2300.…”
Section: Costsmentioning
confidence: 99%
“…It is a common observation that lymphoedema of the toes feet and legs go often unnoticed, leading to inter digital sepsis aggravating the clinical state [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life suffered, with clear deficits in many domains of the well-validated SF-36 questionnaire. 1 …”
Section: Why Is Chronic Oedema Important?mentioning
confidence: 99%